ANALISIS TEKNIS DAN EKONOMIS PRODUKSI TERPADU ARANG DAN CUKA KAYU DARI TIGA JENIS KAYU - Tjutju Nurhayati; Sylviani Sylviani; Mahpudin Mahpudin (Jurnal Penelitian Hasil Hutan, 2003)
Analysis on the integrated production of charcoal and  wood vinegarhas  been conducted using the raw materials  of three wood species, i.e. mangrove (Bruguera sp.), mangium (Acacia mangium), and tusam (Pinus merkusii). As such, those three were each carbonized into charcoal through a direct burning  in a dome kiln with 2 m3 capacity;  and concurrently,  the distillation  through  the cooling of.the generated  gas/vapor fraction  was conducted to collect the wood vinegar. The resulting charcoal werefurther treated  either with or without purification process. To evaluate the qualities of the two products (i.e. charcoal and wood vinegar), the physico-chemical  and economic analyses were examined. Economic analysis covered the collection of data/information on purchasing prices of the equipment.  material-procuring cost for  the kiln, kiln-erection cost. production cost, cost of procuring auxiliary matters,  charcoal and wood vinegar prices,  and others, followed by their assessment. Results of the analysis  were as follows:Integrated production  of charcoal and the one of wood vinegar turned out to be the best with respect to their  technical  aspects and physico-chemical properties was from  the raw material of mangrove  wood species.  In this regard, the yield of charcoal and wood vinegar was the highest. Likewise, the qualities  of the charcoal could correspond to usage standard  of charcoal for iron ore. Also, the qualities of the wood vinegar could meet the Japan Standard Requirement.The implementation of purification treatment on the resulting charcoal could decrease the volatile matter content, and increase fixed carbon content and  calorific  value  without   affecting  the production of  wood  vinegar. As  such,   the  volatile  matter  contents  in mangium charcoal decreased from 27.09 percent  to  17.35   percent,  and  in tusam charcoal from 33.18  percent to 24. 79 percent.Productions of charcoal and wood vinegar for one m3  of wood were in the range of 181- 217 kg and 169 -  205 kg, respectively for mangrove wood;  110  -121 kg and 121 -  125  kg, respectively formangium wood; and 111-121 kg and 141  kg, respectively for tusam wood.Production of charcoal which is in  integration  with the one of wood vinegar can gain  a significant benefit. Such benefit can be achieved after 5 years of wood vinegar production, i.e.  82.6 percent per year from  mangrove wood, and  mangium as well as tusam wood.   Conversely, the production of  wood vinegar in integration with the one of charcoal can gain additional benefit, i.e. 39.7 percent per year from mangrove wood, and 39.9 percent per-year from mangium as well-as-tusam wood. The benefit per year of such integrated  production in the sixth year will be even greater, since the interest payment and loan can be ultimately fulfilled. All  the investment of the factory with implements an integrated production-of  charcoal and wood vinegar can be returned in one year and 3 months.